Victim Participation in Intimate Partner Violence Prosecution - Implications for Safety: Kalamazoo County, Michigan, 1999-2002 - Rhodes, Karin V. ([Verlag nicht ermittelbar], 2014)
This longitudinal mixed-methods study examined to what extent female intimate partner violence (IPV) victim participation in prosecution was associated with their future safety. The study followed a cohort of female IPV victims with cases the police presented to the prosecutor, in the year 2000, in a single Midwestern United States county (Kalamazoo County, Michigan) for a four-year period (1999-2002) across multiple systems (police, prosecutor, criminal court, civil court, hospital Emergency Departments) to assess the victim's experience with participation in IPV prosecution and her associated future help seeking, health and safety. Since this study utilized retrospective administrative data, subsequent IPV was defined as a future documented IPV-related police incident or an Emergency Department visit for IPV or injury. The data abstraction and analysis of the administrative data was informed by focus groups with survivors, advocates, and medical and criminal justice service providers, along with in-depth qualitative analysis of a stratified random sample of individual IPV cases. The final analytic dataset created by the research team integrated two types of data: (1) in-depth data about the index assault case and characteristics of the couple involved, and (2) longitudinal data about prior and subsequent IPV events spanning multiple systems: police, prosecutor, emergency department, and family court protection orders.